Identification of cortical connectivities during isometric contraction with visual stimulation using coherence analysis - 233421 Siti Hajar Aminah Ali; Norlaili Mat Safri (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2007